REVITALIZATION OF ISLAMIC FINANCIAL INSTITUTIONS AND FINTECH INNOVATION: REALIZING PROSPERITY IN LOW-INCOME COMMUNITIES - Rahma, Laila Fitria Nur (Jurnal Al-Iqtishad, 2024)
This study uses a qualitative approach and literature review method to explain related phenomena. The purpose of the study is to provide an overview of the role of Islamic financial institutions and fintech in overcoming poverty. Secondary data were obtained from related literature such as academic journals, books, articles, and other documents. The analysis method used is descriptive analysis with a focus on an in-depth understanding of the phenomenon. The results of the study illustrate that in the perspective of Islamic Economics, poverty is overcome through synergy between the government, Islamic financial institutions, and the community with a social development and empowerment approach. Islamic financial institutions play a key role in managing zakat and sadaqah funds, providing affordable financing, and focusing on community empowerment. FinTech, as a financial technology innovation, has the potential to distribute zakat efficiently, facilitate access to Islamic investment, and increase financial inclusion. However, challenges related to understanding, accessibility, and regulation still need to be overcome. Collaboration between Islamic financial institutions and fintech is expected to overcome these obstacles, create an inclusive financial ecosystem, and support the welfare of low-income communities. The implication of this study is that the integration of financial technology in Islamic financial institutions can make a positive contribution to poverty alleviation and improve community welfare.